Estrategia de aprendizaje musical y empatía en niños de la I.E.P.I. N° 279 Inmaculada Concepción Flore de Punga río Ucayali 2021 - Cachique Soplin, Giovanna (2022)
The main purpose of the research work was to determine the relationship between the musical learning strategy and empathy in children of the I.E.P.I. N.° 279 Immaculate Conception of Flor de Punga on the Ucayali River in 2021. The research methodology considered the descriptive type, through a cross-sectional, field, and univariate design. For data collection, observation was considered as a technique and an observation sheet as a research instrument, which was validated by teachers as expert judges. The study population has been 118 children of initial level, who also made up the sample. In conclusion, it was found that 49.2% who consider the child's empathy as good, also consider the musical learning strategy as good and 28.0% who consider the child's empathy as very good, also consider the learning strategy. music as good. The value of Chi - square = 24.004 p = 0.000 indicates a significant relationship between both variables under study.